Four Digital Electronic Combination Key Using A 74HCT688 Comparator IC Accompanied with An Alarm as A Security - Supriyono; Santoso, Teguh (BEST, 2023)
The development of science and technology is increasingly useful and has a positive impact on providing convenience in all areas of human life, so that various tools, books, information, facilities and others are increasingly new and developing more rapidly. In addition, the development of science and technology also has a negative or detrimental effect on human life, namely the occurrence of various rampant crimes, acts of theft, robbery, bank break-ins that often occur everywhere, for this the key role as a security device becomes very important. Various forms of locks are widely used, both mechanical and electronic, compared to electronic locks, mechanical locks are felt to be less secure for use as door security, a four-digit digital electronic combination lock is designed using a comparator IC 74HCT688 accompanied by an alarm as a door guard